Empirical Analysis of Rehabilitation Programs for Children in Conflict with the Law at Jayapura Class II Juvenile Correctional Facility - Ringgi, Deppa; Amir, Muh. Anugrah Kurniawan (CV. Social Politic Genius (SIGn), 2025)
Amid the paradox between the idealism of humanistic child protection regulations and high recidivism rates, this study examines the effectiveness of rehabilitation programs for children in conflict with the law. This study aims to analyze in-depth how the rehabilitation program at the Jayapura Class II JCF operates as a mechanism to reconstruct social bonds. This process is analyzed using Hirschi’s Social Control Theory as a framework. Applying an empirical legal method with a case study approach, primary data were collected through semi-structured interviews with officers and juvenile residents as well as participatory observation, and were subsequently analyzed qualitatively. The results indicate that the three main programs—physical and spiritual development, social development, and education—work synergistically as an architecture of social engineering to mend and reinforce the four elements of the social bond. Attachment is built through communal structures. Commitment is instilled through investment in orderliness and the development of future skills. Involvement is ensured through a densely structured schedule. Belief is reconstructed through consistent moral education. A crucial finding reveals that although formal education faces structural constraints, the non-formal skills program is more effective in building commitment. It is concluded that the key to successful rehabilitation lies not in the luxury of facilities, but in an institution’s ability to systematically re-weave torn social bonds, which serves as the foundation for the successful rehabilitation and social reintegration of children.